Acute Recreational Noise-Induced Cochlear Synaptic Dysfunction in Humans With Normal Hearing: A Prospective Cohort Study - Wang, Qixuan; Yang, Lu; Qian, Minfei; Hong, Yingying; Wang, Xueling; Huang, Zhiwu; Wu, Hao (Frontiers in Neuroscience, 2021)
Objectives The objective of the study was to identify the acute high-intensity recreational noise-induced effects on auditory function, especially the cochlear synaptopathy-related audiological metrics, in humans with normal hearing. Methods This prospective cohort study enrolled 32 young adults (14 males and 18 females); the mean age was 24.1 ± 2.4 years (ranging from 20 to 29). All participants with normal hearing (audiometric thresholds ≤25 dB HL at frequencies of 0.25, 0.5, 1, 2, 3, 4, 6, and 8 kHz for both ears) had already decided to participate in the outdoor music festival. Participants were asked to measure the noise exposure dose and complete auditory examinations, including the air-conduction pure-tone audiometry (PTA), distortion product otoacoustic emission (DPOAE), contralateral suppression (CS) on transient evoked otoacoustic emission (TEOAE), auditory brainstem response (ABR) test and Mandarin Hearing in Noise Test (MHINT), at baseline and 1 day and 14 days after music festival noise exposure. Results The mean time of attending the music festival was 7.34 ± 0.63 h (ranging from 6.4 to 9.5), the mean time-weighted average (TWA) of noise exposure dose was 93.2 ± 2.39 dB(A) (ranging from 87.9 to 97.7). At neither 1 day nor 14 days post exposure, there were no statistically significant effects on PTA thresholds, DPOAE amplitudes, CS on TEOAEs, or MHINT signal-to-noise ratios (SNRs) of acute outdoor music festival noise exposure, regardless of sex. While the ABR wave I amplitudes significantly decreased at 1 day after exposure and recovered at 14 days after exposure, the exposed/unexposed ABR wave I amplitude ratio was significantly correlated with MHINT SNR change at 1 day after exposure, although it was not correlated with the noise exposure dose. Conclusion In young adults with normal hearing, we found the self-compared decrement of ABR wave I amplitudes at 1 day post acute recreational noise exposure at high intensity, which also contributes to the change in speech perceptual ability in noisy backgrounds. This study indicated that auditory electrophysiological metric changes might be a more sensitive and efficient indicator of noise-induced cochlear synaptic dysfunction in humans. More attention should be paid to the recreational noise-induced cochlear synaptopathy and auditory perceptual disorder.